2023
DOI: 10.21203/rs.3.rs-2966278/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breeding corals for heat tolerance

Adriana Humanes,
Liam Lachs,
Elizabeth Beauchamp
et al.

Abstract: Marine heatwaves are becoming more frequent, widespread and severe1, leading to mass coral bleaching and mortality. Yet it remains unknown whether natural coral adaptation can keep pace with climate warming2. As a result, selective breeding has been proposed to enhance coral heat tolerance3. The viability of this management solution hinges on the extent of heritability of coral heat tolerance. We show that selecting parent colonies for heat tolerance results in higher tolerance of adult offspring. This result … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…increases the potential for new coral cover by an order of magnitude relative to the base case we consider in this study. However, a very high value of V = 0.5 • C 2 is inconsistent with empirical data (43,44).…”
Section: Disproportionate Impact Of Climate Change On Acroporid Coral...mentioning
confidence: 59%
See 2 more Smart Citations
“…increases the potential for new coral cover by an order of magnitude relative to the base case we consider in this study. However, a very high value of V = 0.5 • C 2 is inconsistent with empirical data (43,44).…”
Section: Disproportionate Impact Of Climate Change On Acroporid Coral...mentioning
confidence: 59%
“…As previously described, light limitation and acidification contribute to the limited capac- The additive genetic variance (with respect to the coral thermal optimum) is poorly constrained, although a growing number of studies have found phenotypic variance that translates into additive genetic variance V of order 0.05 • C 2 (43,44). Greater additive genetic variance reduces the predicted fall in coral cover over the 21 st century (figure S26), due to faster evolution.…”
Section: Disproportionate Impact Of Climate Change On Acroporid Coral...mentioning
confidence: 90%
See 1 more Smart Citation